Effect of Mulching Materials on Yield-Attributing Parameters and Bunch Yield of Cavendish Banana (Musa acuminata cv. ‘Grand Naine’) - Chalise, Basant; Shrestha, Arjun Kumar; Srivastava, Arvind; Tripathi, Kalyani Mishra (Nepalese Horticulture, 2024)
A field experiment was conducted at DoAR, Khajura, Banke, Nepal to find the effect of different types of mulching materials on yield and yield-attributing parameters of ‘Grand Naine’ banana for the two cropping periods, 2020-2021 and 2021-2022. The field was laid out in RCBD having seven treatments replicated three times. Tissue culture plants were planted at 2×2 m spacing in 16 m2 plots, where there were four plants per plot. FYM and chemical fertilizers were applied @ 20 kg and 250:250:350 g NPK per plant per crop cycle along with 0.5% ZnSO4, 0.2% FeSO4, 0.2% CuSO4, and 0.1% Borax was applied as a foliar spray at 3rd, 5th and 7th months after planting. Among the different types of mulches, the bunch length (120.60 cm), distance between first and final hand of bunch (75.50 cm), number of hands (10.00), weight of second hand (3.13 kg), finger length (22.57 cm), girth (13.75 cm), and weight (171.90 g), bunch weight (24.30 kg), and yield (60.76 t ha-1) were recorded the highest with banana leaves mulch which was closely followed by black plastic mulch. The results of the experiment revealed that as compared to un-mulched plots, mulched plots produced the better yield-attributing parameters and yield of banana. Therefore, banana growers are recommended to use banana leaves as a mulching materials for higher yield. As an alternative, black plastic mulch can used for effective moisture retention and weed control, minimizing soil erosion and higher bunch yield.